Systems engineering demystified : apply modern, model-based systems engineering techniques to build complex systems - Holt, Jon (Expert insight., 2023)
Systems engineering helps in developing and describing complex systems. Written by an internationally-recognized systems engineering expert, this updated edition provides insight into elements to consider when designing a complex system that is robust and successful. The latest edition covers the new approaches of Model-Based Systems Engineering (MBSE) and its deployment techniques using the Trinity approach. You will learn about the system engineering life cycle and processes to implement. Effective systems can be built only when the system is designed with close attention to detail, meaning each aspect of the system is recognized and understood before the system is built. The book explains in great detail, different system models and visualization techniques, with a focus on SysML, to help you visualize a system in the design phase. You will also learn various verification and validation techniques to ensure your system design is ready to be implemented. The book ends with key management processes, systems engineering best practices, and guidelines, with a new section on effective approaches based on the author's impressive 30 years of experience in the field. By the end of this systems engineering book, you'll be able to apply modern model-based systems engineering techniques to your own systems and projects. This book is for aspiring systems engineers, engineering managers, or anyone looking to apply systems engineering practices to their systems and projects. While a well-structured, model-based approach to systems engineering is an essential skill for engineers of all disciplines, many companies are finding that new graduates have little understanding of MBSE. This book helps you acquire this skill with the help of a simple and practical approach to developing successful systems. No prior knowledge of systems engineering or modeling is required to get started with this book.